Comparing the Oncological Risk of Hormonal and Non-Hormonal Contraceptives in Cervical Cancer: A Literature Review - Haifa Hasna Putri; Fiona Paramitha (CV. Publikasi Indonesia, 2026)
Cervical cancer is a malignancy with high morbidity and mortality rates among women worldwide, including Indonesia. While high-risk HPV (hr-HPV) infection is the primary cause, contraceptive use is strongly suspected to act as a significant cofactor in cervical carcinogenesis. This research aims to analyze the comparison of cervical cancer risk between hormonal and non-hormonal contraceptive use through a comprehensive literature review. The study design was a literature review with a systematic search strategy on PubMed and Google Scholar databases. Ten original research articles (5 national and 5 international journals) published between 2016 and 2026 were selected based on inclusion and exclusion criteria. The analysis results showed that 60% of the studies reported a significant association between long-term hormonal contraceptive use ≥ 5 years and an increased risk of cervical cancer, with Odds Ratio (OR) values ranging from 2.4 to 7.0. In contrast, non-hormonal contraceptive use, specifically the Intrauterine Device (IUD), consistently showed a lower risk profile or provided a protective effect against pre-cancerous lesions. However, some studies showed variations influenced by confounding factors such as age at first marriage and parity. Long-term hormonal contraceptive use is associated with an increased risk of cervical cancer, while non-hormonal contraceptives (IUD) have a better oncological safety profile. Comprehensive counseling and routine screening (VIA/Pap Smear) are required for contraceptive acceptors, especially long-term hormonal method users.